A damage mechanics based on the constitutive model for strain-softening rocks. (July 2019) - Shen, Peiwu; Tang, Huiming; Ning, Yibing; Xia, Ding
Highlights: A damage constitutive model based on Weibull distribution and unified strength theory is developed. The evolution of damage in rocks is analysed which reflects the damaging extent of rocks. The physical meanings of model parameters are proved to correspond to reality. Abstract: The deformation-induced damage of rocks in underground space always results in the long-term instability of engineering projects. In this paper, a damage mechanics based on the constitutive model related to the Weibull distribution and unified strength theory is developed. This model considers the statistical damage, strain softening and damage weakening of rocks in the deformation process. To verify the feasibility of this model, the model parameters were mathematically confirmed, four experimental examples were cited to illustrate the features of the axial pressure versus axial strain under various confining pressures, and five experimental examples were cited to compare the distinction of the axial pressure obtained from the proposed model versus the confining pressure with Mohr-Coulomb criterion. Then, the evolution of damage in the deformation process was analyzed based on the proposed model. Finally, the physical meanings of the model parameters were discussed. The results mainly reveal that the proposed model has a good consistency with the experimental examples, the evolution of damage contains three stages with the deformation process, and the model parameters have distinct physical meanings.